2014
DOI: 10.1055/s-0034-1370015
|View full text |Cite
|
Sign up to set email alerts
|

Tiefe Hirnstimulation in der Psychiatrie: Ethische Aspekte

Abstract: Deep brain stimulation (DBS) has been shown to be an efficacious treatment for many neurological conditions and has thus been expanded to psychiatric diseases as well. Following an introduction on the history of DBS in psychiatry, this review summarizes commonly raised ethical concerns and questions on clinical trial design, selection of patients, informed consent and concerns about the possible impact of DBS on an individual's personality. Finally, it highlights the fact that critique on DBS in psychiatry is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…The crucial role of the NAc in reward processing makes it a promising target for interventions aimed at modulating dysregulated reward circuitry, such as treatment for SUD. Previous studies on DBS of NAc have demonstrated promising treatment effects in SUD that can greatly reduce substance craving after stimulations (Muller et al, 2013;Coles et al, 2018;Luigjes et al, 2019;Hassan et al, 2021). For this reason, we selected NAc as the target for sonication.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The crucial role of the NAc in reward processing makes it a promising target for interventions aimed at modulating dysregulated reward circuitry, such as treatment for SUD. Previous studies on DBS of NAc have demonstrated promising treatment effects in SUD that can greatly reduce substance craving after stimulations (Muller et al, 2013;Coles et al, 2018;Luigjes et al, 2019;Hassan et al, 2021). For this reason, we selected NAc as the target for sonication.…”
Section: Discussionmentioning
confidence: 99%
“…Deep brain stimulation (DBS) of the NAc as a treatment for SUD is still in its preliminary stages, with only case reports and case series. Although early, the limited data available signals DBS of the NAc may be a procedure with significant therapeutic potential for the treatment of SUD, with long-term improvement or complete resolution in nearly all 25 subjects and remission rates seen as high as 50% at 6 years (Muller et al, 2013;Coles et al, 2018;Luigjes et al, 2019;Hassan et al, 2021). While promising, DBS requires an extensive invasive neurosurgical procedure with an implantable medical device, indicating long-term monitoring by a clinician.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, although only a few patients with addiction have been included in clinical trials worldwide so far, the simple idea of treating addiction with neuromodulation led to multiple considerations regarding ethical issues. Respective publications tried to propose guidelines for future research but also raised concerns about brain stimulation for 'behavioral' disorders (sometimes even questioning the neurobiological aspects of addiction) or simply disapproved of the idea of treating addiction with brain stimulation [6][7][8][9][10][11][12]. This article describes the results and long-term experiences of 5 patients who received DBS to treat their severe and treatment-resistant addiction.…”
Section: Introduction ▼mentioning
confidence: 99%